Groundwater Salinity and Particulate Organic Carbon Flux Control Benthic Habitats in Anchialine Environments on Millennial Timescales - Cresswell, Jacque N.; van Hengstum, Peter J. (Frontiers in Marine Science, 2022)
The environmental conditions and habitats in Bermudian underwater caves have responded to vertical aquifer migration and groundwater salinity changes associated with sea-level rise since the last glacial maximum. Recently, a large database of modern benthic foraminifera in Bermudian caves were found to be highly sensitive to both the amount and source of particle organic carbon (POC) transported to the sediment-water interface, consistent with similar timewise analysis of foraminifera in a Mexican flooded cave. Here we provide evidence that while benthic meiofaunal communities in Bermuda’s underwater caves are primarily controlled by groundwater salinity changes on millennial timescales from sea-level change, they are secondarily controlled by the POC source and supply deposited in the cave through time. Benthic foraminiferal assemblages were evaluated in the best-preserved stratigraphic succession currently known from an underwater cave. In the case of Palm Cave, POC flux changes were driven by changes in seawater-groundwater circulation dynamics caused by flooding on the carbonate banktop, and the inherited geometry of the cave system itself. These results demonstrate that benthic meiofaunal communities in anchialine environments are highly sensitive to changes in the source and quantity of POC through time. This work also enables a better understanding of the environmental conditions associated with preserved meiofaunal remains in global cave sediment. These results indicate that if the POC flux to the subsurface increases from coastal urbanization on karst landscapes, subsurface anchialine communities are likely to respond.